Pengaruh Strategi Pembelajaran Quiz Team Terhadap Hasil Belajar Matematika Ditinjau Dari Gaya Belajar Kinestetik Kelas XI Semester Genap Di SMAN 1 Ngemplak Tahun Ajaran 2015/2016 - FATIMAH, FRIDA NOOR; , Dr. Sumardi, M.Si (2016)
Frida Noor Fatimah / A410120021. Influence of Learning Strategies Quiz Team on Mathematics Learning Outcomes Observed from Kinesthetic Learning Styles Class XI Semester at SMAN 1 Ngemplak.. Research Paper. Faculty of Teaching and Education Training. Muhammadiyah University of Surakarta. March. 2016.. The aim of research to describe and analyze: (1) the influence of mathematics learning with learning strategies quiz team and learning strategies Conventional (2) the effect of kinesthetic learning style of students to the learning outcomes of mathematics, (3) the interaction between the learning strategies and kinesthetic learning style of students with learning outcomes mathematics. This research is a quasi experimental with experimental design. The study population was all students of class XI SMAN 1 Ngemplak the second semester of the 2015/2016 academic year. The study sample consisted of two classes. The sampling technique using cluster random sampling. The test method usage data collection and documentation. Data were analyzed by analysis of variance with two different cell lines. The results of the data analysis with a significance level of 5% was obtained: (1) there is the influence of learning strategies Quiz Team and conventional learning strategies, with F_A = 5151 (2) there is the effect of kinesthetic learning style to the learning outcomes of mathematics, with F_B = 20 649 (3) there is no interaction between the learning strategies Quiz Team and conventional learning strategies based with kinesthetic learning style of students with mathematics learning outcomes, with F_AB = 0230.